CO-DETERMINATION AND APPRENTICESHIP IN SME: A QUALITATIVE STUDY ON WORK COUNCILS AND THEIR CONTRIBUTION TO THE QUALITY OF APPRENTICESHIP TRAINING - Eberhardt, Christiane; Berger, Klaus (Professional Pedagogics, 2020)
Relevance. Training systems which are based on the principle of apprenticeship and involve the company as a central venue are gaining in significance in international terms. The fundamental recognition here is, “Apprenticeships as one successful form of work-based learning ease the transition from education and training to work, and evidence suggests that countries with a strong VET and apprenticeship system have lower levels of youth unemployment” (Euro-pean Commission, year of publication not stated).Aim: the purpose of the article is to prove that the competitiveness of companies on the market crucially depends on their skilled workers.Methods: іn methodological terms, we based our study on an industrial sociology case study approach.Results: іn our study we showed that the stakeholders at the companies forming the object of our investigations are working towards quality. If the high quality requirements of training are also to be realised at a company level, crucial significance needs to be attached to the central players within the company. In our case, these are the works councils.Conclusions: іn our study, we have shown that “good training” can be equated with the terms of “vocational proficiency” and “matching”. This combination, which aims both to impart employability skills and to facilitate inte-gration into the company, provides the bedrock which enables skilled workers to act autonomously and independently. Works councils bring their influence to bear if they believe that these principles are in jeopardy. This makes an essential contribution to integrating apprentices into a company in respect of skills and socialisation.
Keywords: аpprenticeship training within the dual system; Germany; social partnership; co-determination; work councils; training in SME